VIDEOLAPAROSCOPIC PROPYLACTIC SALPINGOOOPHORECTOMY: INITIAL EXPERIENCE - Vieira, Sabas Carlos; Fontinele, Danilo Rafael da Silva (Mastology, 2020)
Introduction: The BRCA mutation substantially increases the risk of ovarian cancer, from 20% to 60% when the mutation is in BRCA1, and 10% to 20% in BRCA1. Bilateral salpingo-oophorectomy may be the most important intervention in these patients, with clear impact on the reduction of mortality caused by ovarian cancer, and about 85% to 50% of reduction in the incidence of breast cancer. Salpingo-oophorectomy should be performed from the ages of 35 to 40 in patients with BRCA1 mutation, and after the age of 40 for BRCA2 carriers. Objectives: To present our initial experience of prophylactic bilateral salpingo-oophorectomy in patients with BRCA mutation. Method: This is a retrospective study. We included all patients who had tested positive for the BRCA mutation assisted from 1999 to 2019. Seven patients were identified with BRCA mutation and underwent videolaparoscopic salpingo-oophorectomy. The procedure was classic. The pieces were removed in endobags and sent to histological analysis with serial sections. The study was approved by the Research Ethics Committee, report n. 2.817.502. Results: No tumor was found in the surgical piece. The mean age of patients when they underwent surgery was 45.8 years. The patients, together, added 21 cases of breast cancer and 4 cases of ovarian cancer among 1st, 2nd and 3rd degree relatives. Five (71.4%) patients presented with BRCA1 mutation. Three patients had been diag-nosed with breast cancer, none with previous ovarian cancer. As to the surgery: 3 (42.8%) also underwent bilateral or con-tralateral risk-reducing mastectomy with reconstruction, and 4 (57.2%) only underwent bilateral salpingo-oophorectomy. All patients are alive and without an active oncologic disease, with mean follow-up of 32 months. Conclusions: In this sample, we did not find any occult tumor in patients submitted to bilateral salpingo-oophorectomy due to BRCA mutation.